2001
DOI: 10.1007/s002390010256
|View full text |Cite
|
Sign up to set email alerts
|

Identifications, Classification, and Evolution of the Vertebrate α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionic Acid (AMPA) Receptor Subunit Genes

Abstract: The AMPA receptor (AMPAR), a pharmacologically defined ionotropic glutamate receptor, mediates fast excitatory synaptic transmission in the vertebrate central nervous system. Mammalian and avian AMPARs are assembled from the products of four genes (GRIA1-GRIA4) conserved in their translated sequences and gene organizations. Teleost fish also express AMPAR subunits; however, the AMPAR genes have not been extensively investigated in lower vertebrates. To elucidate the evolution of vertebrate AMPAR genes, reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…Potential candidate genes for consideration include: the tryptophan oxygenase gene (TDO2) 45 and potentially genes encoding a glycine receptor (GLRB) 46 and glutamate receptor (GRIA2). 47 We observed a second peak on chromosome 4 at marker D4S3051 on 4q35 (NPL ¼ 2.43, Po0.01). This region overlaps with a report by Adams et al 48 who found a parametric LOD ¼ 3.19 under a dominant model and broad affection status.…”
Section: Discussionmentioning
confidence: 94%
“…Potential candidate genes for consideration include: the tryptophan oxygenase gene (TDO2) 45 and potentially genes encoding a glycine receptor (GLRB) 46 and glutamate receptor (GRIA2). 47 We observed a second peak on chromosome 4 at marker D4S3051 on 4q35 (NPL ¼ 2.43, Po0.01). This region overlaps with a report by Adams et al 48 who found a parametric LOD ¼ 3.19 under a dominant model and broad affection status.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, Ciona has only Ca-P GluAs throughout its life span because ciGluAs are the sole AMPA-type receptor in this species. Other invertebrates, such as nematodes and flies, have also been reported to have only Q-type GluAs (50). The requirement for Ca-I GluAs in mammals appears to be evolutionarily unique and may be related to the role of GluAs in synaptic transmission acquired during the evolution of vertebrates.…”
Section: Resultsmentioning
confidence: 99%
“…6A, right). This additional band might be a homologue of GluR2, because the teleost brain contains multiple homologues of a single gene of mammalian AMPA receptor (Chen et al, 2001). Alternatively, the additional band might represent a different glycosylation form or a splicing form.…”
Section: Immunoblotting and Immunohistochemistry For Glutamate Receptorsmentioning
confidence: 93%